PENGARUH SUPERVISI PENDIDIKAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR DI MAWASANGKA TENGAH - Sulaeman; Rahmat Hidayat; Syamsul Alam (Halu Oleo University, 2025)
This study aims to analyze the effect of educational supervision conducted by school principals on the performance of elementary school teachers in Mawasangka Tengah District. The research used a quantitative method with a deductive approach and a positivist paradigm. The study involved 68 elementary school teachers from nine schools in Mawasangka Tengah District, selected through simple random sampling. Data were collected using a Likert-scale questionnaire that had undergone validity and reliability testing. Data analysis was performed using linear regression with the assistance of IBM SPSS Statistics 26. The findings indicated that educational supervision conducted by school principals has a positive and significant effect on the performance of elementary school teachers (p = 0.000), with an R = 0.692 indicating a strong relationship and R Square = 0.479 showing that 47.9% of the variation in teacher performance is influenced by educational supervision. These findings align with theoretical literature and previous studies that highlight the importance of professional support and feedback in educational supervision. However, challenges such as geographical accessibility and limited facilities also need to be addressed. Based on these results, it can be concluded that educational supervision by school principals plays a significant role in improving the performance of elementary school teachers in Mawasangka Tengah District.